Carte des nouvelles decouvertes au nord de la Mer du Sud: tant à l'Est de la Sibérie et du Kamtchatka, qu'à l'Ouest de la Nouvelle France. - Santini, Francesco (Chez François Santini, 1776)
Map shows routes of exploration, areas of Native American habitation, and major settlements; western New France [northwestern portion of North America] includes "Mer ou Baye de l'Ouest" possibily as an early and enormous representation of Vancouver Bay; dates and names of explorers/discoverers. Includes "Avertissement," illustrations, and title cartouche. Relief shown pictorially. Scale not given.